Immunoproteomics and phage display in the context of leishmaniasis complexity - Ludolf, Fernanda; Ramos, Fernanda F.; Coelho, Eduardo A. F. (Frontiers in Immunology, 2023)
Leishmaniasis is defined as a complex of diseases caused by protozoan parasites of the genus Leishmania, which comprises 20 parasite species pathogenic to mammalians, such as humans and dogs. From a clinical point-of-view, and considering the diversity and biological complexity of the parasites, vectors and vertebrate hosts; leishmaniasis is classified according to the distinct clinical manifestations, such as: tegumentary (involving the cutaneous, mucosal and cutaneous-diffuse forms) and visceral leishmaniasis. Many issues and challenges remain unaddressed, which could be attributed to the complexity and diversity of the disease. The current demand for the identification of new Leishmania antigenic targets for the development of multicomponent-based vaccines, as well as for the production of specific diagnostic tests; is evident. In recent years, biotechnological tools have allowed to the identification of a number of Leishmania biomarkers with potential application as vaccine and diagnosis. In this review, we propose to discuss the different aspects of this complex disease addressed by technologies as immunoproteomics and phage display, and what solutions they brought. It is very important to be aware of the objective for which antigens where screening, in order to use them properly, understanding their performance, characteristics, and self-limitations.